Preparation method and application of stannous sulfide / copper-tin sulfide nano semiconductor heterostructure with sheet structure and enzyme-like activity

A solvothermal and precipitation method enhances copper tin sulfide nanomaterials' enzyme-like activity, addressing low activity issues and enabling efficient enzyme catalysis and high-sensitivity cancer marker detection.

CN119219054APending Publication Date: 2024-12-31HARBIN ENG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411393070.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing copper tin sulfide nanomaterials exhibit low enzyme-like activity, limiting their application in the biomedical field, and traditional preparation methods are energy-intensive, polluting, and difficult to produce heterostructures.

Method used

A solvothermal method combined with a simple precipitation technique is used to create a stannous sulfide/copper tin sulfide nano-semiconductor heterostructure with a sheet structure, enhancing enzyme-like activity by ensuring full substrate contact and reducing energy consumption.

Benefits of technology

The method produces a heterostructure with a larger specific surface area, enabling efficient enzyme catalysis and rapid detection of cancer markers with high sensitivity and a lower detection limit, readable by the naked eye.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219054A_ABST
    Figure CN119219054A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a stannous sulfide / copper-tin sulfide nano semiconductor heterostructure with a sheet structure and enzyme-like activity, and relates to a preparation method of a nano semiconductor heterostructure. The problem that an existing copper-tin sulfide nano material is low in enzyme activity is solved. The method comprises the following steps: 1, stirring and mixing SnCl2. 2H2O, thiourea, anhydrous citric acid and ethylene glycol; 2, heating and preserving heat to obtain a brown green turbid liquid; 3, adding deionized water into the brown green turbid liquid, then centrifuging to remove supernate, collecting precipitate to obtain flower-shaped SnS crystals, centrifugally washing and drying, and finally dissolving the flower-shaped SnS crystals into ethanol to obtain ethanol suspension of the flower-shaped SnS crystals; and 4, ultrasonic treatment. The invention is applied to enzyme catalysis and detection of cancer markers. The preparation method is used for preparation and application of the stannous sulfide / copper-tin sulfide nano semiconductor heterostructure with the sheet structure and the enzyme-like activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a nanometer semiconductor heterostructure. Background Art

[0002] As a photoelectric conversion material with excellent performance, tin sulfide (SnS) exhibits high photoelectric conversion efficiency and absorption characteristics that are highly matched to the solar spectrum. Therefore, it is regarded as a potential alternative material for traditional platinum counter electrodes in dye-sensitized solar cells, which is expected to significantly reduce production costs. In addition, SnS is also a typical thermoelectric material. Through specific preparation processes or element doping strategies, its thermoelectric properties can be greatly regulated, showing broad application prospects in aerospace, national defense, military, and waste heat recovery.

[0003] Copper tin sulfide, as an important type of ternary chalcogenide semiconductor material derived from SnS, has high carrier mobility and a suitable optical band gap, making it an ideal choice for solar cell materials. However, in the field of biology, there are relatively few studies on the application of copper tin sulfide materials, especially the exploration of their enzyme-like activity. Given the low biological toxicity of copper tin sulfide, its application potential in the biomedical field is worth looking forward to. Unfortunately, its low enzyme-like activity limits its further expansion in this field.

[0004] Traditionally, copper tin sulfide is mainly prepared into bulk or thin film forms by methods such as powder sintering or vapor deposition, which are very suitable for the application scenarios of optoelectronic devices. However, these methods not only have high energy consumption and use highly polluting binders, but also have limited material surface and cannot provide sufficient substrate contact for enzyme-like active sites, thus greatly limiting their catalytic performance. In recent years, with the continuous development of copper tin sulfide materials in the energy field, methods such as hydrothermal method, solvothermal method, sol-gel method, and high-temperature thermal decomposition method have emerged to prepare copper tin sulfide with high specific surface area, which have successfully achieved the preparation of nano-scale particles and even quantum dots, and obtained electrode materials with good substrate contact area. However, most of these methods involve the preparation of copper tin sulfide heterostructures, which require complex and cumbersome in-situ growth techniques, resulting in difficult production technology and high production costs; in addition, there are currently no reports on the activity of copper tin sulfide heterostructure enzymes. Summary of the invention

[0005] The present invention aims to solve the problem of low enzyme activity of existing copper tin sulfide nanomaterials, and further provide a preparation method and application of a stannous sulfide / copper tin sulfide nanosemiconductor heterostructure with a sheet structure and enzyme-like activity.

[0006] A method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure with a sheet structure and enzyme-like activity is carried out according to the following steps:

[0007] 1. Under the condition of temperature of 60°C to 80°C, SnCl2·2H2O, thiourea, anhydrous citric acid and ethylene glycol are stirred and mixed to obtain a mixed solution;

[0008] 2. Keep the mixed solution at 160°C to 180°C for 15 to 20 hours, then cool it to room temperature to obtain a brown-green suspension;

[0009] 3. Add deionized water to the brown-green suspension, then centrifuge to remove the supernatant, collect the precipitate to obtain flower-like SnS crystals, centrifuge and wash the flower-like SnS crystals, dry them, and finally dissolve them in ethanol to obtain an ethanol suspension of flower-like SnS crystals;

[0010] Fourth, under the condition of ultrasonic power of 150W to 300W, the ethanol suspension of flower-shaped SnS crystals was ultrasonically treated for 20min to 60min using an ultrasonic cell disruptor, and then the supernatant was collected by low-speed centrifugation, and finally the supernatant was centrifuged at high speed to obtain a precipitate and dried to obtain flaky SnS crystals;

[0011] 5. Suspend the flaky SnS crystals in deionized water, then ultrasonically treat for 30 min to 45 min at a power of 200 W to 300 W, then add CuCl2 aqueous solution at a dropping speed of 1 mL / min to 3 mL / min, and continue ultrasonically treating for 1.5 h to 2 h at a power of 200 W to 300 W. Finally, collect the precipitate by centrifugation, wash it by centrifugation, and dry it to obtain a stannous sulfide / copper tin sulfide nanosemiconductor heterostructure with a flaky structure and enzyme-like activity.

[0012] Applications, it is used in enzyme catalysis and detection of cancer markers.

[0013] The beneficial effects of the present invention are:

[0014] The present invention adopts a solvothermal method and a simple precipitation method to prepare a SnS / Cu4SnS4 nanoheterostructure with a sheet structure and enzyme-like activity (POD activity), and is used for enzyme catalysis and rapid detection of cancer markers, having the following advantages:

[0015] 1. Compared with most SnS and Cu4SnS4 materials, this sheet-like heterostructure has a larger specific surface area, which can make the active sites (Cu + ) fully contacts with the substrate to accelerate the catalytic efficiency.

[0016] 2. Different from the previously reported high-temperature thermal decomposition and solvothermal heterostructure growth methods, the present invention uses a simple precipitation method to complete the in-situ growth of Cu4SnS4 on SnS, which is simpler and more convenient to operate and reduces energy utilization.

[0017] 3. This heterostructured nanomaterial has good peroxidase (POD)-like activity and can efficiently catalyze the oxidation of the POD substrate 3,3',5,5'-tetramethylbenzidine (TMB) to form a blue product with strong absorption at 652nm. It can be used as the signal amplification core in rapid detection to achieve high-sensitivity detection, that is, a lower detection limit.

[0018] Fourth, the electrons of tin and sulfur in the heterostructure prepared by this method will spontaneously migrate to copper, thereby increasing the electron density near the copper atom and accelerating the catalytic process of Cu. 2+ Reduction to Cu + process, improving the overall catalytic ability.

[0019] 5. The sheet-like nanoheterostructure has absorption in the entire visible spectrum, so it can provide an obvious black color signal as a label in rapid detection, and the rapid detection test paper is readable by the naked eye.

[0020] Instruction Manual

[0021] Figure 1 Transmission electron microscope (TEM) images of samples at different stages in Example 1, a is the flower-like SnS crystal prepared in step 3, b is the sheet-like SnS crystal prepared in step 4, and c is the SCS3 nanosheet prepared in step 5;

[0022] Figure 2 This is a scanning transmission electron microscope (STEM) element distribution diagram of the SCS3 nanosheet prepared in Example 1;

[0023] Figure 3 This is a high-resolution TEM image of the SCS3 nanosheet prepared in Example 1;

[0024] Figure 4 X-ray diffraction (XRD) patterns of the flower-like SnS crystals (FSnS) prepared in step 3 of Example 1, the flake SnS crystals (SnS) prepared in step 4, the SCS3 nanosheets prepared in step 5, and the flake Cu4SnS4 nanocrystals prepared in the comparative experiment;

[0025] Figure 5 The high-resolution X-ray photoelectron spectroscopy (XPS) analysis results of samples at different stages of Example 1, a is the Cu 2p spectrum of the SCS3 nanosheets prepared in step 5, and b is the S2p spectrum of the flaky SnS crystals prepared in step 4 and the SCS3 nanosheets prepared in step 5;

[0026] Figure 6 The low-temperature nitrogen adsorption-desorption isotherm and the corresponding adsorption pore size distribution of the SCS3 nanosheet prepared in Example 1, a is the low-temperature nitrogen adsorption-desorption isotherm, and b is the adsorption pore size distribution;

[0027] Figure 7 The absorption spectrum of the SCS3 nanosheets prepared in Example 1 at visible light wavelengths and the catalytic performance comparison diagram of samples with different CuCl2·2H2O addition amounts, a is the absorption spectrum of the SCS3 nanosheets at visible light wavelengths in aqueous solutions of different concentrations, and b is a comparison diagram of the catalytic performance of samples with different CuCl2·2H2O addition amounts in Examples 1 to 3 at pH = 5 using TMB as a probe;

[0028] Figure 8 The catalytic ability of the SCS3 nanosheets prepared in Example 1 and the electron spin resonance (ESR) spectra of the SCS3 nanosheets prepared in Example 1, the SCS1 nanosheets prepared in Example 2, and the sheet SnS crystal prepared in step 4 of Example 1 evaluated with TMB as a probe under different pH conditions, a is the catalytic ability of the SCS3 nanosheets under different pH conditions, and b is the ESR spectrum;

[0029] Fig. 9 The enzymatic kinetic characteristic diagram of the SCS3 nanosheet prepared in Example 1, a is the change trend of the absorbance of the solution over time at different hydrogen peroxide concentrations; b is the Michaelis-Menten curve, and c is the Lineweaver-Burk curve;

[0030] Fig.10 The initial colorimetric signals of the test paper prepared by SCS3 nanosheets at different CEA concentrations, a is the calibration curve of the initial signal, b is the enlarged view of the linear interval and the linear fitting diagram, and c is the actual photo of the test paper for detecting samples with different CEA concentrations;

[0031] Fig.11 The photothermal signals of the test paper prepared by SCS3 nanosheets at different CEA concentrations, a is the calibration curve of the photothermal signal, b is the logarithmic transformation and linear fitting diagram of the horizontal axis, and c is the thermal imaging photos of the test paper of samples with different CEA concentrations;

[0032] Fig.12 The enhanced colorimetric signal of the test paper prepared by SCS3 nanosheets at different CEA concentrations, a is the calibration curve of the enhanced colorimetric signal, b is the logarithmic transformation and linear fitting diagram of the horizontal axis, and c is the enhanced colorimetric photo of the samples with different CEA concentrations. DETAILED DESCRIPTION

[0033] Specific implementation method 1: This implementation method is a method for preparing a tin sulfide / copper tin sulfide nano-semiconductor heterostructure with a sheet structure and enzyme-like activity, which is carried out according to the following steps:

[0034] 1. Under the condition of temperature of 60°C to 80°C, SnCl2·2H2O, thiourea, anhydrous citric acid and ethylene glycol are stirred and mixed to obtain a mixed solution;

[0035] 2. Keep the mixed solution at 160°C to 180°C for 15 to 20 hours, then cool it to room temperature to obtain a brown-green suspension;

[0036] 3. Add deionized water to the brown-green suspension, then centrifuge to remove the supernatant, collect the precipitate to obtain flower-like SnS crystals, centrifuge and wash the flower-like SnS crystals, dry them, and finally dissolve them in ethanol to obtain an ethanol suspension of flower-like SnS crystals;

[0037] Fourth, under the condition of ultrasonic power of 150W to 300W, the ethanol suspension of flower-shaped SnS crystals was ultrasonically treated for 20min to 60min using an ultrasonic cell disruptor, and then the supernatant was collected by low-speed centrifugation, and finally the supernatant was centrifuged at high speed to obtain a precipitate and dried to obtain flaky SnS crystals;

[0038] 5. Suspend the flaky SnS crystals in deionized water, then ultrasonically treat for 30 min to 45 min at a power of 200 W to 300 W, then add CuCl2 aqueous solution at a dropping speed of 1 mL / min to 3 mL / min, and continue ultrasonically treating for 1.5 h to 2 h at a power of 200 W to 300 W. Finally, collect the precipitate by centrifugation, wash it by centrifugation, and dry it to obtain a stannous sulfide / copper tin sulfide nanosemiconductor heterostructure with a flaky structure and enzyme-like activity.

[0039] This specific embodiment adopts a simple precipitation method for the first time, and successfully obtains SnS / Cu4SnS4 nano-heterostructures with flake morphology, high active surface area and excellent enzyme-like activity in aqueous solution under a mild temperature environment. The obtained flake structure, due to its large surface area, is conducive to the effective attachment and growth of Cu4SnS4, while ensuring the full display of active sites, thereby significantly enhancing the enzyme-like activity. Specifically, the SnS nanosheets obtained by ultrasonic treatment show a larger specific surface area than the flower-like SnS, providing a rich growth base for the construction of heterostructures and promoting the formation of more heterogeneous interfaces. In addition, the interaction between copper ions and the SnS substrate promotes the simultaneous generation of Cu4SnS4 phases in multiple crystals, thereby forming ultra-fine Cu4SnS4 grains and allowing the active sites to be fully exposed. Furthermore, the electrons of sulfur atoms and tin atoms in the SnS phase spontaneously migrate to copper atoms, resulting in an increase in the electron density around copper atoms. This effect accelerates the rate in the catalytic reaction, thereby significantly improving the catalytic efficiency.

[0040] The beneficial effects of this embodiment are:

[0041] In this embodiment, a SnS / Cu4SnS4 nanoheterostructure with a sheet structure and enzyme-like activity (POD activity) is prepared by a solvothermal method and a simple precipitation method, and is used for enzyme catalysis and rapid detection of cancer markers, with the following advantages:

[0042] 1. Compared with most SnS and Cu4SnS4 materials, this sheet-like heterostructure has a larger specific surface area, which can make the active sites (Cu + ) fully contacts with the substrate to accelerate the catalytic efficiency.

[0043] 2. Different from the previously reported high-temperature thermal decomposition and solvothermal heterostructure growth methods, this embodiment uses a simple precipitation method to complete the in-situ growth of Cu4SnS4 on SnS, which is simpler and more convenient to operate and reduces energy utilization.

[0044] 3. This heterostructured nanomaterial has good peroxidase (POD)-like activity and can efficiently catalyze the oxidation of the POD substrate 3,3',5,5'-tetramethylbenzidine (TMB) to form a blue product with strong absorption at 652nm. It can be used as the signal amplification core in rapid detection to achieve high-sensitivity detection, that is, a lower detection limit.

[0045] Fourth, the electrons of tin and sulfur in the heterostructure prepared by this method will spontaneously migrate to copper, thereby increasing the electron density near the copper atom and accelerating the catalytic process of Cu. 2+ Reduction to Cu + process, improving the overall catalytic ability.

[0046] 5. The sheet-like nanoheterostructure has absorption in the entire visible spectrum, so it can provide an obvious black color signal as a label in rapid detection, and the rapid detection test paper is readable by the naked eye.

[0047] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that: the mass ratio of SnCl2·2H2O to thiourea in step 1 is 1:(1-2); the mass ratio of SnCl2·2H2O to anhydrous citric acid in step 1 is 1:(1-4); the mass ratio of SnCl2·2H2O to ethylene glycol in step 1 is 0.45 g:(60-120) mL. Others are the same as specific embodiment 1.

[0048] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the volume ratio of the brown-green suspension to deionized water in step 3 is 1:(1-1.5). Other aspects are the same as specific implementation method 1 or 2.

[0049] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: the centrifugal removal of supernatant described in step 3 is specifically performed at a speed of 3500r / min to 4000r / min for 1min to 7min; the centrifugal washing described in step 3 is specifically performed at a speed of 3500r / min to 4000r / min using deionized water and anhydrous ethanol as washing liquids for 1min to 2min at a speed of 3500r / min to 4000r / min; the drying described in step 3 is specifically performed at a vacuum condition of 60°C to 65°C for 10h to 12h. The rest is the same as specific embodiments 1 to 3.

[0050] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the concentration of the flower-shaped SnS crystals in the ethanol suspension of the flower-shaped SnS crystals in step 3 is 8 mg / mL to 12 mg / mL. The rest is the same as specific embodiments 1 to 4.

[0051] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: during the ultrasonic treatment in step 4 and step 5, the ultrasonic treatment is performed for 1s to 2s and then the ultrasonic treatment is turned off for 1s to 2s. The rest is the same as specific embodiments 1 to 5.

[0052] Specific implementation method 7: This implementation method is different from the specific implementation methods 1 to 6 in that: the low-speed centrifugation to collect the supernatant in step 4 is specifically centrifuged at a speed of 3500r / min to 4000r / min for 1min to 2min; the high-speed centrifugation of the supernatant to obtain the precipitate in step 4 is specifically centrifuged at a speed of 10000r / min to 12000r / min for 8min to 10min; the drying in step 4 is specifically dried at a vacuum condition of 60℃ to 65℃ for 10h to 12h. The rest is the same as the specific implementation methods 1 to 6.

[0053] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: the mass ratio of the flaky SnS crystals described in step 5 to the volume of deionized water is 1g:(400-500)mL; the mass ratio of the flaky SnS crystals described in step 5 to the CuCl2·2H2O in the CuCl2 aqueous solution is 1:(0.38-5.65); the concentration of CuCl2·2H2O in the CuCl2 aqueous solution described in step 5 is 10mg / mL-20mg / mL. Others are the same as specific embodiments 1 to 7.

[0054] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: the centrifugal collection of precipitation described in step 5 is specifically carried out at a rotation speed of 10000r / min to 12000r / min for 8min to 10min; the centrifugal washing described in step 5 is specifically carried out at a rotation speed of 10000r / min to 12000r / min using deionized water and anhydrous ethanol as washing liquids for 8min to 10min; the drying described in step 5 is specifically carried out at a vacuum condition of 60℃ to 65℃ for 10h to 14h. The rest is the same as specific embodiments 1 to 8.

[0055] Specific embodiment 10: This embodiment is an application of a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure with a sheet structure and enzyme-like activity, which is used for enzyme catalysis and detection of cancer markers.

[0056] The following examples are used to verify the beneficial effects of the present invention:

[0057] Embodiment 1:

[0058] A method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure with a sheet structure and enzyme-like activity is carried out according to the following steps:

[0059] 1. Under the conditions of a temperature of 60°C and a stirring speed of 300 rpm / min, SnCl2·2H2O, thiourea, anhydrous citric acid and ethylene glycol were stirred and mixed for 30 minutes to obtain a mixed solution;

[0060] The mass ratio of SnCl2·2H2O to thiourea is 1:1; the mass ratio of SnCl2·2H2O to anhydrous citric acid is 1:4; the mass ratio of SnCl2·2H2O to ethylene glycol is 0.45 g:120 mL;

[0061] 2. Raise the temperature of the mixed solution to 180°C at a rate of 5°C / min, and keep the temperature at 180°C for 18 hours, then cool to room temperature to obtain a brown-green suspension;

[0062] 3. Add deionized water to the brown-green suspension, then centrifuge to remove the supernatant, collect the precipitate to obtain flower-shaped SnS crystals, centrifuge and wash the flower-shaped SnS crystals, and finally dissolve them in ethanol to obtain an ethanol suspension of flower-shaped SnS crystals;

[0063] The volume ratio of the brown-green suspension to deionized water is 1:1; the concentration of the flower-shaped SnS crystals in the ethanol suspension of the flower-shaped SnS crystals is 10 mg / mL;

[0064] Fourth, under the condition of ultrasonic power of 300W, the ethanol suspension of flower-shaped SnS crystals was ultrasonically treated for 30min using an ultrasonic cell disruptor, and the ultrasonic treatment was performed for 2s and then turned off for 1s, and then the supernatant was collected by low-speed centrifugation, and finally the supernatant was centrifuged at high speed to obtain a precipitate and dried to obtain flaky SnS crystals;

[0065] 5. Suspend the SnS flake crystals in deionized water, and then ultrasonicate them for 0.5 h at a power of 200 W, and turn off the ultrasound for 1 second every 2 seconds during the ultrasonication. Then, add the CuCl2 aqueous solution at a drop rate of 2 mL / min, and continue ultrasonicating for 1.5 h at a power of 200 W, and turn off the ultrasound for 1 second every 2 seconds during the ultrasonication. Finally, collect the precipitate by centrifugation, wash it by centrifugation, and dry it, so as to obtain a SnS / Cu4SnS4 nano-semiconductor heterostructure with a flake structure and enzyme-like activity, which is named SCS3 nanosheet.

[0066] The mass ratio of the flaky SnS crystals to the volume of deionized water is 1 g:400 mL; the mass ratio of the flaky SnS crystals to CuCl2·2H2O in the CuCl2 aqueous solution is 1:3.39; and the concentration of CuCl2·2H2O in the CuCl2 aqueous solution is 16.95 mg / mL.

[0067] The centrifugal removal of supernatant described in step three is specifically performed at a speed of 4000r / min and centrifuged for 7min; the centrifugal washing described in step three is specifically performed using deionized water as a washing liquid, at a speed of 4000r / min, centrifugation washing for 1min, deionized water washing twice, and then using anhydrous ethanol as a washing liquid, at a speed of 4000r / min, centrifugation washing for 1min, and anhydrous ethanol washing twice; the drying described in step three is specifically performed under vacuum conditions at a temperature of 65°C and dried for 12h.

[0068] The low-speed centrifugation to collect the supernatant in step 4 is specifically centrifuged at a speed of 4000 rpm / min for 1 min; the high-speed centrifugation to obtain the precipitate in step 4 is specifically centrifuged at a speed of 12000 r / min for 8 min; the drying in step 4 is specifically dried at a vacuum condition of 65° C. for 12 h;

[0069] The centrifugal collection of precipitation described in step five is specifically performed at a rotation speed of 12000r / min and centrifuged for 8min; the centrifugal washing described in step five is specifically performed using deionized water as a washing liquid, at a rotation speed of 12000r / min, centrifugation washing for 8min, deionized water washing twice, and then using anhydrous ethanol as a washing liquid, at a rotation speed of 12000r / min, centrifugation washing for 8min, and anhydrous ethanol washing twice; the drying described in step five is specifically performed under vacuum conditions at a temperature of 65°C and dried for 12h.

[0070] Example 2: This example is different from Example 1 in that the mass ratio of the SnS sheet crystals to the CuCl2·2H2O in the CuCl2 aqueous solution in step 5 is 1:1.13; the tin sulfide / copper tin sulfide nano-semiconductor heterostructure with sheet structure and enzyme-like activity prepared in step 5 is named SCS1 nanosheet. The rest is the same as Example 1.

[0071] Example 3: This example is different from Example 1 in that the mass ratio of the flaky SnS crystals to the CuCl2·2H2O in the CuCl2 aqueous solution in step 5 is 1:5.65; the tin sulfide / copper tin sulfide nano-semiconductor heterostructure with flaky structure and enzyme-like activity prepared in step 5 is named SCS5 nanosheet. The rest is the same as Example 1.

[0072] Comparative experiment: The difference between this comparative experiment and Example 1 is that the mass ratio of the flaky SnS crystals described in step 5 to the CuCl2·2H2O in the CuCl2 aqueous solution is 1:45.2; in step 5, the CuCl2 aqueous solution is added at a drop rate of 2mL / min, and the ultrasonic treatment is continued for 6h at a power of 150W; and in step 5, the flaky Cu4SnS4 nanocrystals are completely replaced to obtain the flaky Cu4SnS4 nanocrystals, which are named Cu4SnS4. The rest is the same as Example 1.

[0073] Figure 1 The transmission electron microscope (TEM) images of the samples at different stages in Example 1, a is the flower-like SnS crystal prepared in step 3, b is the sheet-like SnS crystal prepared in step 4, and c is the SCS3 nanosheet prepared in step 5. In Figure a, a flower-like SnS morphology composed of a large number of sheet-like structures loosely assembled can be observed. Figure b shows the irregular sheet-like morphology of SnS after ultrasonic crushing, with a size of about 300 nanometers. Figure c reveals the morphology after the Cu4SnS4 phase growth, in which the sheet-like matrix is ​​densely covered with irregular small dot-like crystals, which indicates that Cu4SnS4 nucleates simultaneously in multiple places to form ultrafine dot-like crystals.

[0074] Figure 2This is a scanning transmission electron microscope (STEM) element distribution diagram of the SCS3 nanosheet prepared in Example 1. As can be seen from the figure, the surface of the SCS3 nanosheet is relatively rough, and the Sn, S and Cu elements are evenly distributed in the nanosheet, which confirms the uniform growth of the Cu4SnS4 phase on the surface of the SnS substrate.

[0075] Figure 3 This is a high-resolution TEM image of the SCS3 nanosheets prepared in Example 1. The image clearly shows the high crystallinity of the SCS3 nanosheets, with distinct lattice fringes. Specifically, the interplanar spacing d = 0.282nm corresponds to the (111) crystal plane of SnS, while d = 0.32nm corresponds to the (121) crystal plane of Cu4SnS4, which preliminarily verifies the successful nucleation and growth of Cu4SnS4 on the SnS substrate.

[0076] Figure 4 The X-ray diffraction (XRD) patterns of the flower-shaped SnS crystals (FSnS) prepared in step 3 of Example 1, the sheet-shaped SnS crystals (SnS) prepared in step 4, the SCS3 nanosheets prepared in step 5, and the sheet-shaped Cu4SnS4 nanocrystals prepared in the comparative experiment are shown in the figure. The patterns show that the XRD diffraction peaks of the flower-shaped and sheet-shaped SnS are highly consistent with the diffraction peak positions in the standard card, proving that the synthesized SnS crystals are pure phase. At the same time, the diffraction peaks of the SCS3 nanosheets retain the characteristic peaks of the SnS substrate, and two smaller additional peaks appear at 28.5° and 33.5°. These two peaks can be respectively attributed to the (102) and (321) crystal planes of Cu4SnS4, further confirming the successful nucleation and growth of Cu4SnS4 on the SnS substrate.

[0077] Figure 5 The high-resolution X-ray photoelectron spectroscopy (XPS) analysis results of samples at different stages of Example 1, a is the Cu 2p spectrum of the SCS3 nanosheets prepared in step 5, and b is the S2p spectrum of the sheet-like SnS crystals prepared in step 4 and the SCS3 nanosheets prepared in step 5. Figure 5 a, The main valence state of Cu in SCS3 nanosheets is +1. In particular, Cu 2p 3 / 2 The peak position is located at 932 eV, showing a lower binding energy compared to the standard peak position, which indicates that there is an electron enrichment effect around the copper atoms. Figure 5 b reveals that the S2p XPS spectrum of SCS3 nanosheets can be subdivided into four absorption peaks, corresponding to the S2p in SnS and SnS2 crystals, respectively. 1 / 2 and S2p 3 / 2 It is worth noting that the position of the S2p peak in SCS3 shifts toward a higher binding energy compared to the S2p peak in SnS, which confirms the migration of S atom electrons.

[0078] Figure 6 The low-temperature nitrogen adsorption-desorption isotherm and the corresponding adsorption pore size distribution of the SCS3 nanosheets prepared in Example 1, a is the low-temperature nitrogen adsorption-desorption isotherm, and b is the adsorption pore size distribution. Figure 6 a shows that SCS3 nanosheets exhibit a typical type IV adsorption isotherm, which is a characteristic of mesoporous materials, with a specific surface area of ​​45.7815 m 2 / g. Figure 6 b shows that the pore size distribution of SCS3 nanosheets is mainly concentrated around 4 nm, further confirming its mesoporous structural characteristics.

[0079] TMB (3,3',5,5'-tetramethylbenzidine) was used as a probe to evaluate the peroxidase-like (POD) activity of SnS / Cu4SnS4 nanosemiconductor heterostructures with sheet-like structures and enzyme-like activities. The experimental steps are as follows: First, SCS1 nanosheets, SCS3 nanosheets, or SCS5 nanosheets were dispersed in 0.02M acetate buffer (pH = 2 to 11) to obtain a solution with a concentration of 40μg / mL (1.3mL); at the same time, H2O2 was diluted to 200mM (1.5mL) using the same acetate buffer, and TMB was dissolved in DMSO to a concentration of 3mg / mL (0.2mL). Subsequently, these solutions were mixed and reacted for 5min. Afterwards, the absorbance of the mixed solution was measured using a UV-visible spectrophotometer.

[0080] Using DMPO (5,5-dimethyl-1-pyrroline-N-oxide) as a probe, the free radical generation ability of SnS / Cu4SnS4 nano-semiconductor heterostructures with sheet structures and enzyme-like activity was evaluated. The experimental steps are as follows: SCS1 nanosheets prepared in Example 2, SCS3 nanosheets prepared in Example 1, or sheet-like SnS crystals prepared in step 4 of Example 1 are dispersed in deionized water to form a 100 μg / mL solution (20 μL), and then mixed with hydrogen peroxide solution (mass fraction 30%, 10 μL) and DMPO (5 μL) and then sucked into a capillary and injected to test the electron spin resonance spectrum.

[0081] Figure 7The absorption spectrum of the SCS3 nanosheets prepared in Example 1 at visible light wavelengths and the catalytic performance comparison diagram of samples with different CuCl2·2H2O addition amounts, a is the absorption spectrum of the SCS3 nanosheets at visible light wavelengths in aqueous solutions of different concentrations, and b is a comparison diagram of the catalytic performance of samples with different CuCl2·2H2O addition amounts in Examples 1 to 3 at pH = 5 using TMB as a probe. Figure a is the absorption spectrum of the SCS3 sample in the visible light region. It can be seen that the SCS3 sample has uniform absorption in the visible light region, so the result observed by the naked eye is obviously black. Figure b is a comparison diagram of the catalytic performance of samples with different CuCl2·2H2O addition amounts. The results show that there is a blue product with strong absorption at 652nm, and under the condition of pH = 5, the mass ratio of the flaky SnS mass to the CuCl2·2H2O mass ratio in Example 1 is 1:3.39, and the catalytic performance reaches the best.

[0082] Figure 8 The catalytic ability of the SCS3 nanosheets prepared in Example 1 and the electron spin resonance (ESR) spectra of the SCS3 nanosheets prepared in Example 1, the SCS1 nanosheets prepared in Example 2 and the sheet SnS crystal prepared in step 4 of Example 1 evaluated with TMB as a probe under different pH conditions, a is the catalytic ability of the SCS3 nanosheets under different pH conditions, and b is the ESR spectrum. Figure 8 a shows the absorbance of the mixed solution at 652 nm after 5 minutes of reaction under different pH conditions. It can be clearly observed that when pH = 5, the absorbance reaches the highest value, indicating that under this pH condition, the POD-like activity of SCS3 nanosheets is the strongest. Figure 8 b compares the ESR spectra of the SCS3 nanosheets prepared in Example 1, the SCS1 nanosheets prepared in Example 2, and the sheet-like SnS crystals prepared in step 4 of Example 1 after mixing with H2O2 and DMPO indicators. Among them, the SCS3 nanosheet group shows an obvious 1:2:2:1 hydroxyl radical characteristic peak, and the peak height signal is the strongest, which indicates that the SCS3 nanosheet has a stronger hydroxyl radical generation ability than SCS1.

[0083] TMB was used as a probe to investigate the enzymatic kinetic characteristics of SnS / Cu4SnS4 nano-semiconductor heterostructures with sheet-like structures and enzyme-like activities. The specific experimental process is as follows: First, SCS3 nanosheets were dispersed in 0.02M, pH=5 acetate buffer to prepare a 12μg / mL dispersion (1.8mL); then, H2O2 was diluted to different concentrations (1mL) using the same buffer, and TMB was dissolved in DMSO to form a 10mg / mL solution (0.2mL). The three solutions were mixed evenly to form mixed solutions with final hydrogen peroxide concentrations of 0.33mM, 1mM, 1.67mM, 3.33mM, 10mM, 16.67mM and 33.33mM, respectively, and immediately placed in a UV-visible spectrophotometer to monitor the change in absorbance at 652nm over time.

[0084] Fig. 9 The enzymatic kinetics of the SCS3 nanosheets prepared in Example 1 is shown in Figure 1. a is the absorbance variation trend of the solution over time at different hydrogen peroxide concentrations; b is the Michaelis-Menten curve, and c is the Lineweaver-Burk curve. According to the fitting results, the Km value of the SCS3 nanosheets for H2O2 is 0.921 mM, and the Vmax value is 0.224×10 -7 M / s. This data indicates that SCS3 nanosheets have a very high affinity for H2O2, thus exhibiting excellent POD-like activity.

[0085] In order to verify the performance of SnS / Cu4SnS4 nano-semiconductor heterostructure with sheet structure and enzyme-like activity, it was applied to the LFIA rapid detection of CEA. The specific method is as follows:

[0086] 1. Preparation of immune probe: First, 3 mg of SCS3 nanosheets were ultrasonically dispersed in 5 mL of anhydrous ethanol and mixed with 5 mL of anhydrous ethanol solution containing 50 mg of PTMP-PMAA. After stirring for 4 hours, carboxyl-functionalized SCS3@PP was obtained by centrifugal washing. Then, SCS3@PP was dispersed in 5 mL of morpholineethanesulfonic acid (MES) buffer (0.02 M, pH = 6), 90 μg of CEA antibody 2 was added, and after stirring for 0.5 hour at 2°C to 4°C in the dark, 150 μL of LEDC solution was added and stirred for another 0.5 hour. Then, a 10% bovine serum albumin (BSA) solution was added and stirred for 2 hours. The precipitate was collected by centrifugation and redissolved in 1 mL of preservation solution (0.02 M pH = 7.4 acetate buffer, containing 25% sucrose, 0.3% Pc-300 and 2% BSA) to obtain the SCS3-Ab2 probe; the PTMP-PMAA was prepared according to the patent with authorization announcement number CN117025209B and invention name "An orange silver fluorescent probe for detecting tetracycline antibiotics and its preparation method".

[0087] 2. Preparation of LFIA rapid test paper: Spray the SCS3-Ab2 probe onto the sealed glass fiber membrane at a parameter of 6 μL / cm and dry it as a sample pad, then dilute the CEA antibody 1 and goat anti-rabbit immunoglobulin with coating solution (0.02M pH = 7.4 acetate buffer, containing 2% sucrose) to obtain 0.6 mg / mL CEA antibody 1 solution and 0.6 mg / mL goat anti-rabbit immunoglobulin solution, draw two lines on the nitrocellulose membrane at a process parameter of 1 μL / cm, and after drying, assemble in the order of back plate-nitrocellulose membrane-sample pad-absorbent pad, cut into 3 mm wide test strips and press into the card shell;

[0088] 3. For the detection of CEA carcinoembryonic antigen, a calibration curve is prepared based on the proportional dilution of the pure product. The sample is diluted 5 times with a working solution (0.02M pH = 7.4 acetate buffer, containing 0.02% BSA), and 80 μL is added to the sample well. After 15 minutes of chromatography, the signal is read with a dry fluorescent immunoassay analyzer. The photothermal signal is obtained by measuring the maximum temperature of the T line after 1 minute of 1W, 808nm laser irradiation with a thermal imaging machine. For the enhanced signal, the 3mm part before and after the T line is cut off, and 200 μL of enhancement solution (4MH2O2 and 6mg / mL TMB, volume ratio of 5:1) is added. After shaking and incubating for 20 minutes, the absorbance at 652nm is tested with an enzyme marker as the signal.

[0089] Figure 10-12 Three signal results of the test strips for detecting samples with different CEA concentrations are shown respectively.

[0090] Fig.10Figure 3 is the initial colorimetric signal of the test paper prepared using SCS3 nanosheets at different CEA concentrations. a is the calibration curve of the initial signal, b is the enlarged view of the linear interval and the linear fitting diagram, and c is the actual photo of the test paper for detecting samples with different CEA concentrations. Figure b shows that the detection limit is 0.258 ng / mL.

[0091] Fig.11 The photothermal signal of the test paper prepared by SCS3 nanosheets at different CEA concentrations, a is the calibration curve of the photothermal signal, b is the logarithmic transformation and linear fitting diagram of the horizontal axis, and c is the thermal imaging photo of the test paper for different CEA concentration samples. The detection limit is 0.505ng / mL as shown in Figure b.

[0092] Fig.12 The enhanced colorimetric signal of the test paper prepared by SCS3 nanosheets at different CEA concentrations, a is the calibration curve of the enhanced colorimetric signal, b is the logarithmic transformation and linear fitting diagram of the horizontal axis, and c is the enhanced colorimetric photo of the samples with different CEA concentrations. The detection limit is 0.209ng / mL as shown in Figure b.

[0093] Combining the results of the three signals, it can be seen that the detection limit of the initial colorimetric signal is sufficient to determine whether the CEA index is abnormal, but its linear range is relatively small (0.5-10 ng / mL); although the detection limit of the photothermal signal is slightly increased, it can cover a larger detection range (1-40 ng / mL); and the enhanced colorimetric signal further reduces the detection limit while maintaining a detection range equivalent to that of the photothermal signal (1-40 ng / mL).

Claims

1. A method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity, characterized in that It is carried out in the following steps:

1. Under the condition of temperature of 60°C to 80°C, SnCl2·2H2O, thiourea, anhydrous citric acid and ethylene glycol are stirred and mixed to obtain a mixed solution; 2. Keep the mixed solution at 160°C to 180°C for 15 to 20 hours, then cool it to room temperature to obtain a brown-green suspension; 3. Add deionized water to the brown-green suspension, then centrifuge to remove the supernatant, collect the precipitate to obtain flower-like SnS crystals, centrifuge and wash the flower-like SnS crystals, dry them, and finally dissolve them in ethanol to obtain an ethanol suspension of flower-like SnS crystals; Fourth, under the condition of ultrasonic power of 150W to 300W, the ethanol suspension of flower-shaped SnS crystals was ultrasonically treated for 20min to 60min using an ultrasonic cell disruptor, and then the supernatant was collected by low-speed centrifugation, and finally the supernatant was centrifuged at high speed to obtain a precipitate and dried to obtain flaky SnS crystals; 5. Suspend the flaky SnS crystals in deionized water, then ultrasonically treat for 30 min to 45 min at a power of 200 W to 300 W, then add CuCl2 aqueous solution at a dropping speed of 1 mL / min to 3 mL / min, and continue ultrasonically treating for 1.5 h to 2 h at a power of 200 W to 300 W. Finally, collect the precipitate by centrifugation, wash it by centrifugation, and dry it to obtain a stannous sulfide / copper tin sulfide nanosemiconductor heterostructure with a flaky structure and enzyme-like activity.

2. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that The mass ratio of SnCl2·2H2O to thiourea in step one is 1:(1-2); the mass ratio of SnCl2·2H2O to anhydrous citric acid in step one is 1:(1-4); the mass ratio of SnCl2·2H2O to ethylene glycol in step one is 0.45 g:(60-120) mL.

3. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that The volume ratio of the brown-green suspension described in step 3 to deionized water is 1:(1-1.5).

4. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that The centrifugal removal of supernatant described in step three is specifically performed at a rotation speed of 3500r / min~4000r / min, and centrifuged for 1min~7min; the centrifugal washing described in step three is specifically performed using deionized water and anhydrous ethanol as washing liquids, respectively, at a rotation speed of 3500r / min~4000r / min, and centrifuged for 1min~2min; the drying described in step three is specifically performed at a vacuum condition of 60℃~65℃, and dried for 10h~12h.

5. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that The concentration of the flower-shaped SnS crystals in the ethanol suspension of the flower-shaped SnS crystals in step 3 is 8 mg / mL to 12 mg / mL.

6. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that During the ultrasonic treatment in step 4 and step 5, the ultrasound was applied for 1s to 2s each and then turned off for 1s to 2s.

7. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that The low-speed centrifugation to collect the supernatant in step 4 is specifically performed at a speed of 3500 r / min to 4000 r / min, and the centrifugation is performed for 1 min to 2 min; the high-speed centrifugation to obtain the precipitate in step 4 is specifically performed at a speed of 10000 r / min to 12000 r / min, and the centrifugation is performed for 8 min to 10 min; the drying in step 4 is specifically performed at a vacuum condition of 60°C to 65°C, and the drying is performed for 10 h to 12 h.

8. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that The mass ratio of the flaky SnS crystals described in step five to the volume of deionized water is 1g:(400-500)mL; the mass ratio of the flaky SnS crystals described in step five to CuCl2·2H2O in the CuCl2 aqueous solution is 1:(0.38-5.65); the concentration of CuCl2·2H2O in the CuCl2 aqueous solution described in step five is 10mg / mL-20mg / mL.

9. The method for preparing a stannous sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity according to claim 1, characterized in that The centrifugal collection of the precipitate described in step five is specifically performed at a rotation speed of 10000 r / min to 12000 r / min, and centrifuged for 8 min to 10 min; the centrifugal washing described in step five is specifically performed using deionized water and anhydrous ethanol as washing liquids, respectively, at a rotation speed of 10000 r / min to 12000 r / min, and centrifuged for 8 min to 10 min; the drying described in step five is specifically performed at a vacuum condition of 60° C. to 65° C., and dried for 10 h to 14 h.

10. Use of a tin sulfide / copper tin sulfide nano-semiconductor heterostructure having a sheet structure and enzyme-like activity as prepared according to claim 1, characterized in that It is used in enzyme catalysis and detection of cancer markers.